Shaping An Exemplary Individual: Implementing Project-Based Learning In Religious Education Courses At Public Universities - Ulum, Bachrul; Satria, Aditya Pringga; Zaini, Mohammad; Riswadi, Riswadi; Amrullah, Zen (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
The current generation of young people plays a pivotal role in advancing Indonesia towards its vision of a Golden Indonesia by 2045. Within the realm of higher education, particularly in religious studies, there exists a significant emphasis on cultivating the character of students. Islamic education, in particular, holds a crucial position in the development of competent individuals equipped with both technical skills and interpersonal competencies. This research endeavors to explore the implementation of project-based learning (PjBL) within the curriculum of Religious Education programs offered by public universities. The aim is to harness this approach as a means of fostering exemplary student character. Conducted in Tulungagung, Indonesia, this study adopts a qualitative methodology employing a case study design. Semi-structured interviews were carried out with key stakeholders in education as well as experts in Islamic religious education at the university level. Additionally, participatory observation and document analysis were utilized to scrutinize the integration of project-based learning within the religious education curriculum. Findings from this research indicate that the incorporation of the PjBL approach into Religious Education courses at public universities facilitates an interactive and collaborative learning atmosphere. By engaging in practical projects aligned with religious contexts and local customs, students are allowed to cultivate practical skills and a profound comprehension of religious principles and local traditions crucial to the development of exemplary character.   Keywords: Religious Education, Public Universities, Project-Based Learning, Character Development